Assessing the Epidemiological Data and Management Methods of Body Packers Admitted to a Referral Center in Iran. Issue 19 (May 2016) - Alipour-faz, Athena; Shadnia, Shahin; Mirhashemi, Seyyed Hadi; Peyvandi, Maryam; Oroei, Mahbobeh; Shafagh, Omid; Peyvandi, Hassan; Peyvandi, Ali Asghar
Abstract : Abstract: The incidence of smuggling and transporting illegal substances by internal concealment, also known as body packing, is on the rise. The clinical approach to such patients has been changed significantly over the past 2 decades. However, despite a recorded increase in body packing in general, there are controversies in the management of these patients. We aimed to gather data regarding the demographic characteristics, treatment, and outcome of body packers, which were that referred to Loghman Hakim Hospital, Tehran, Iran. The data of all body packers admitted to Loghman Hakim Hospital during 2010 to 2014 were evaluated retrospectively. Data regarding the demographic characteristics of the patients, findings of clinical imaging, treatment, and outcome were recorded. In this study, 175 individuals with a mean age of 31 ± 10 years were assessed. The most common concealed substances were crack (37%), crystal (17%), opium (13%), and heroin (6%). According to the results of surgery and imaging (abdominal radiography or computed tomography), the most common place for concealment was stomach in 33.3% and 12% of cases, respectively. Imaging findings were normal in 18% of the individuals. Forty-eight (27%) patients underwent surgery. The main indications for surgery were clinical manifestations of toxicity (79%) and obstruction of the gastro-intestinal tract (17%). The most common surgical techniques were laparotomy and gastrotomy (50%). The mean duration of hospitalization was 3.8 ± 4 days. The mortality rate was 3%. Conservative treatment of body packers seems to be the best treatment method. Careful monitoring of the patients for possible signs and symptoms of intoxication and gastro-intestinal obstruction is strongly recommended.